In depth analysis of the association of FTO SNP (rs9939609) with the expression of classical phenotype of PCOS: a Sri Lankan study - Umayal Branavan; Sulochana Wijesundera; Vishvanath Chandrasekaran; Carukshi Arambepola; Chandrika Wijeyaratne (BMC, 2020)
Abstract Background PCOS is a common disorder of women due to genetic, endocrine and environmental effects that manifests from puberty. The rs9939609 variant of fat mass and obesity associated (FTO) gene is linked to metabolic derangement in PCOS. We previously identified FTO (rs9939609) as a susceptibility locus for PCOS among Sri Lankan women and also explored the role of kisspeptin. Associated factors of the FTO candidate gene among South Asians with PCOS are unknown. Methods This study aimed to determine the association between FTO (rs9939609) polymorphism with clinical (BMI, acanthosis nigricans, hirsutism) and biochemical (serum kisspeptin and testosterone levels) characteristics of PCOS in a cohort of Sri Lankan women. Genetic and clinical data including serum kisspeptin and testosterone concentrations of our previously reported cases (n = 55) and controls (n = 110) were re-analyzed, specifically for an association with rs9939609 variant of FTO gene. Results Logistic regression analysis (AA - OR = 5.7, 95% CI = 2.41-13.63, p < 0.05) and genetic inheritance analysis (AA - OR = 5.49, 95%CI = 2.34-12.88, p < 0.05) showed that FTO (rs9939609) polymorphism is significantly associated with PCOS and its metabolic manifestations. Serum testosterone was significantly higher in affected women with mutant genotypes (AA+AT) than with the normal allele (TT) (p < 0.05). Although serum kisspeptin was higher in subjects with PCOS and mutant alleles than controls, this difference was not significant (p > 0.05). Conclusion FTO gene variant rs9939609 is associated with hyperandrogenemia and metabolic manifestations of PCOS among women of Sri Lankan descent with the well-characterized phenotype. Serum kisspeptin and the FTO genotypes lack a significant association when adjusted for confounders.